Analysis Of Implementation Of Health Operational Assistance (BOK) In Efforts To Improve Mother And Child Health At Gunung Tinggi Puskesmas UPT - Shifah Sagala, Rizqa Auliyah; Rahmah Fadlilatu Syahadah; Medina Elly Vanda; Elva Hariyani; Indah Doanita Hasibuan (Sean Institute, 2024)
Health Operational Assistance (BOK) is implemented to support the implementation of promotive/preventive Puskesmas operations for the community. The lack of BOK funds provided by the Central Government to Districts and Community Health Centers means that Community Health Centers often minimize funding for activities. This research is a qualitative research. Data collection was carried out by in-depth interviews with informants regarding the application of communication factors, resources, disposition and bureaucratic structure.The informants in this research consisted of the main informants: BOK managers, KIA coordinators, Heads of Community Health Centers and triangulation informants of mothers who had toddlers. The qualitative data instrument is an open interview. Qualitative analysis was analyzed using triangulation. The research results showCommunity health centers that utilize BOK optimally for all efforts to improve MCH are carried out in accordance with technical guidelines. The implementation of communication factors, resources, disposition and bureaucratic structure at the UPT Puskesmas Gunung Tinggi is quite good, but the quality of the KIA implementing officers and the BOK team at the UPT Puskesmas Gunung Tinggi is still lacking. In carrying out his duties, he is still assisted a lot by other officers. The understanding of the BOK technical guidelines is clear, the implementation of activities is in accordance with the report, there is involvement of implementers in preparing the POA and there is evaluation in the implementation of activities. Apart from that, in successful Community Health Centers, activity implementers also compile complete supporting data so that making reports is not only the responsibility of the Community Health Center's BOK Management Team.